Pemberdayaan Ekonomi Masyarakat Melalui Open Booth UMKM RW 8 Kelurahan Rungkut Tengah - Ervia Okta Izzatul M; Annisa Lailatul B; Noor Rizkiyah (Yayasan Daarul Huda Kruengmane, 2023)
The increasing demand for living necessities has become a polemic for Indonesian people at this time, the need for clothing and food has increased while income has decreased, the difficulty of getting a job has become a trigger for household inequality in Indonesia. Micro, Small and Medium Enterprises (MSMEs) are a strong mainstay to support the current economy, with products that vary in the processed sector, wet food, healthy drinks, and handicrafts that people can rely on. MSMEs RW 08, Rungkut Tengah Village, assisted by group 90 KKN-T students, MBKM, East Java